2017
DOI: 10.3390/su9040675
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Influences of the D/H Ratio, Size, and Facade Design of an Enclosed Square on Its Perceptual Qualities as a Sustainable Urban Space in South Korea

Abstract: This study examines the dominance of the D/H ratio as a design element for an enclosed urban square, long claimed by numerous urban designers. It claims that like the D/H ratio, other design elements significantly affect the perceptual quality of an enclosed square, but their impacts differ according to the context in which they are applied. The study reviews the literature pertaining to enclosures as an urban design strategy and design elements for an enclosed urban square. Then it presents a comparative anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 11 publications
1
18
0
1
Order By: Relevance
“…Computer graphic simulations can improve the accuracy problem of sketching, and they can overcome the difficulties in controlling the influence of the unnecessary factors of photographs. For example, Im and Kim used computer graphic simulations to investigate the effectiveness of design elements for the urban design qualities of urban public squares [ 9 , 10 ]. However, the problems of limited viewing angles and visual distortions remain, and VR technology can contribute to solving these problems.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Computer graphic simulations can improve the accuracy problem of sketching, and they can overcome the difficulties in controlling the influence of the unnecessary factors of photographs. For example, Im and Kim used computer graphic simulations to investigate the effectiveness of design elements for the urban design qualities of urban public squares [ 9 , 10 ]. However, the problems of limited viewing angles and visual distortions remain, and VR technology can contribute to solving these problems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using advanced computer simulation techniques, subsequent studies adopted more realistic urban spaces, even including detailed building façade design, and revealed that 1.33 is ideal [ 38 ]. More recently, Kim conducted an experiment to test the D/H ratio principle with computer-generated images of enclosed urban public squares [ 10 ]. However, the experiment was limited because the simulated images could only cover a limited viewing angle (specifically, vertical).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations